Faktor-Faktor Yang Berhubungan Dengan Kunjungan Ibu Balita - Sihombing, Rosmalita; Harmendo, Harmendo; Edi, Mohammad (TIN: Terapan Informatika Nusantara, 2024)
Posyandu is a form of community-based health effort (UKBM) which is managed and organized together with the community in implementing health development, in order to empower the community and make it easier for the community to obtain basic/social health services to accelerate the reduction in maternal mortality and infant mortality. (Indonesian Ministry of Health, 2013). Coverage of visits by children under five in the Bangka Belitung Islands Province is still less than the target of 80% with the lowest coverage in South Bangka Regency. Visits for toddlers to posyandu in the Rias Health Center working area of South Bangka Regency decreased in 2020 by 67.9%, in 2021 by 61.8%, and in 2022 by 52.6%. To find out the factors related to visits by toddlers to Posyandu in the Rias Health Center Working Area, South Bangka Regency. This research is quantitative research with a cross sectional approach to measure independent variables with dependent variables. The results of this research showed that factors were associated with visits by mothers of toddlers to posyandu in the working area of the Rias Health Center, South Bangka Regency in 2023, distance from the mother's residence (p=0.047) < α (0.05), mother's occupation (p=0.032) < α (0.05), mother's age (p= 0.023) < α (0.05). The most dominant significant relationship was maternal knowledge (p=0.003) with a POR value= 4.727. There is a significant relationship between the variables of maternal education, maternal occupation, maternal knowledge, distance from maternal residence, maternal age, family support and visits by mothers of toddlers to posyandu in the Rias Health Center Working Area, South Bangka Regency in 2023. Meanwhile, the most dominant variable is among the factors. -The factor related to mothers who have toddlers going to posyandu is the mother's knowledge variable which has p=0.03 <α=0.05, POR value= 4.727.